RELATION BETWEEN ADOPTIVNESS OF MOTORICAL SKILLS AND LOWER SOCIAL STATUS SYMBOLS OF THE STUDETS OF IV - VIII CLASS OF ELEMENTARY SCHOOL - Dragan Martinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
During the testing of the differences of the arithmetics mean factors that bstand in relation to motorical skills F test was used. The purpose of this test was to show the relation between the adoptivness of motorical skill on one ( which class they go to, general marks of the studet, marks in physical education, whether the students feel that the knowledge and experience the y gain in pe lessons enough for diong a sport), and the If students do any sport on the other hand. The total of 1002 studets has been questioned in this survey.